TEMATOLOGI: PEMBACAAN TEORITIS TERHADAP SALAH SATU METODE PENELITIAN SASTRA BANDING CLAUDIO GUILLEN - Lusia Kristiasih Dwi Purnomosasi (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2013)
Comparative literature study by Claudio Guillen has basic reason namely Weltliteratur. Guillen did criticism upon it to formulate his own method on comparative literature research. Goethe has inspired him to create the basic assumsion of his theory; the one and the many and the universal and the local as well, upon which the internationality by socio-historical perspectives is conducted to identify the diachronic structure. It will reveal the supranationality within the primary data being compared. A researcher will stand on 5 principles, one of which is thematology where a principle motif of a theme lies as a means of dialog in internationality.Keywords: comparative literature, internationality, diachronic structure, supranationality